2019
DOI: 10.3390/agronomy9060309
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Temporal Agricultural Land-Cover Mapping Using Single-Year and Multi-Year Models Based on Landsat Imagery and IACS Data

Abstract: The spatial distribution and location of crops are necessary information for agricultural planning. The free availability of optical satellites such as Landsat offers an opportunity to obtain this key information. Crop type mapping using satellite data is challenged by its reliance on ground truth data. The Integrated Administration and Control System (IACS) data, submitted by farmers in Europe for subsidy payments, provide a solution to the issue of periodic field data collection. The present study tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Several studies have used the IACS database in recent years, e.g., to classify and assess land use 56,57 and facilitate methodology development for the identification of crop types from satellite data 58,59 . For the purposes of this study, we collected and synthesized parcel-level data on crop cultivation for each reported field in Sweden for 18 years (2003 to 2020).…”
Section: Crop Data From Integrated Administrative and Control Systemmentioning
confidence: 99%
“…Several studies have used the IACS database in recent years, e.g., to classify and assess land use 56,57 and facilitate methodology development for the identification of crop types from satellite data 58,59 . For the purposes of this study, we collected and synthesized parcel-level data on crop cultivation for each reported field in Sweden for 18 years (2003 to 2020).…”
Section: Crop Data From Integrated Administrative and Control Systemmentioning
confidence: 99%
“…However, it requires vast expert knowledge and is strongly influenced by human subjective factors. To overcome these limitations, machine learning and deep-learning algorithms have been applied to the automatic extraction of planting areas [15][16][17][18][19][20][21]. Machine learning [22] algorithms can automatically extract the rules from known data and use these rules to predict unknown data, which can be applied well to different tasks such as classification, regression, and clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Although the above techniques are easier to implement, they may fail to provide comprehensive information regarding changes [32]. It was found that using feature space transformation operation [33,34] can provide additional textural and spatial features to solve the problem of the homologous spectrum and heterogeneous spectrum brought by spectral interpretation and reduce "salt and pepper effects" [35].…”
Section: Introductionmentioning
confidence: 99%